PENGEMBANGAN LKPD BERBASIS REALISTIC MATHEMATICS EDUCATION UNTUK MENINGKATKAN PEMAHAMAN KONSEP SISWA SD PADA PEMBELAJARAN MATEMATIKA - Mardian Hadi Suryanto; Fatkhur Rohman; Ahmad Mahmuri; Nurhanurawati; Sudi Hartono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics learning in elementary schools is often faced with challenges such as low conceptual understanding and student motivation, due to the lack of varied teaching methods and learning media that are less relevant to daily life. The existing Student Worksheets (LKPD) generally only emphasize calculation exercises without involving students in the process of concept discovery, causing students to become passive and their problem-solving abilities to develop suboptimally. This research aims to develop LKPD based on the Realistic Mathematics Education (RME) approach in order to improve third-grade elementary school students' understanding of mathematical concepts in the topic of Place Value of Whole Numbers. The research method used is Research and Development (R&D) with the 4-D model (Define, Design, Develop, Disseminate). The research subjects were 34 third-grade students at SD Negeri 3 Tangkit Serdang, Tanggamus Regency. The research instruments include validation sheets, practicality questionnaires, and learning achievement tests. The validation results show that RME-based LKPD is highly valid (average validation score of 0.9603 across all aspects), very practical to use (average practicality score of 92 from both teachers and students), and effective in improving student learning outcomes (N-Gain score of 85% with very effective criteria). The conclusion of this research is that the developed RME-based LKPD is proven to be valid, practical, and effective in improving elementary school students' mathematical concept understanding. The development of this LKPD is expected to serve as an alternative for teachers in creating more meaningful and contextual mathematics learning.